Contingent Work Rising: Implications for the Timing of Marriage in Japan. Issue 5 (3rd August 2015) - Piotrowski, Martin; Kalleberg, Arne; Rindfuss, Ronald R.
<x xml:space="preserve">Abstract</x> Employment has become increasingly precarious in developed countries, meaning that, for many young adults, jobs provide neither benefits nor security, more work is part time, and employers are increasingly hiring workers from temporary help agencies and contract companies rather than as employees of their own company. These changes in employment relations have profound effects on gender roles and on family transitions of young adults, especially young men and in particular in countries such as Japan, where there are rigid family norms and the male‐breadwinner tradition still prevails. The authors examined the effects of the experience of non‐regular work on the timing of marriage and whether this differs by sex. Using recent life history data from Japan, they found that men working in non‐regular jobs are especially likely to postpone marriage. The implications of the growth of precarious work for changes in work and family institutions in Japan are discussed.